APPLICATION OF A GENERALIZED NET MODEL IN THE COMMUNICATION OF TWO INDEPENDENT TRAFFIC IN FACULTY OF TECHNICAL SCIENCES AT KONSTANTIN PRESLAVSKI UNIVERSITY OF SHUMEN (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In this paper, а generalized net model providing secure communication of two independent network traffic through ISP1 and ISP2 is presented. Also, a generalized net model modelling the communication process in the computer network of the Faculty of Technical Sciences was developed. The aim of the present study is to improve the Faculty network with generalized net model by providing it with greater efficiency and greater flexibility. The main methods in our research are the method of analysis and synthesis and the method of simulation. The application of generalized net in various fields/aspects of science show the possibilities of the mathematical apparatus for modelling various processes. The indexed matrices used provide flexibility for describing and representing the current states of the cores in the positions they fall into.